The psychology of language and communication - Ellis, Andrew; Beattie, Geoffrey (Hove : UK : Psychology press, 1999)
This book presents an informative and entertaining historical perspective, and illustrates the fact that insights gained into controversial problems in other fields and at other times can shed light on many of today's most contentious debates in
includes bibliographical references and index.
Keywords: Psycholinguistics; Communication; Language